Diabetes prevention in primary care: a review of lifestyle interventions, screening, and risk reduction - Abdullah, Marwah Y.; Esmael, Emtenan A.; Alqahtani, Khalid M.; Qahl, Kholoud H.; Alanazi, Naif A.; Alshakhs, Hashim W.; Alayyash, Fahad A.; Almalki, Yousef A.; Alharbi, Mohammed A.; Alharbi, Ahmed I.; Alhamdan, Maram S. (International Journal Of Community Medicine And Public Health, 2023)
Diabetes mellitus, a global health crisis, necessitates effective prevention strategies. The prevalence of diabetes is on a relentless rise, leading to severe complications and imposing a substantial societal burden. Diabetes prevention has taken center stage in the public health arena. The imperative to develop effective strategies for preventing diabetes, particularly type 2 diabetes, has never been more apparent. The primary goal of diabetes screening is to identify individuals at risk of developing the disease, particularly type 2 diabetes. This paper explores the multifaceted landscape of diabetes prevention, emphasizing the role of lifestyle modifications, screening, and risk reduction. Lifestyle modifications encompass dietary changes, physical activity, and behavioral adjustments, forming the foundational approach. Screening, with various methods and risk assessment tools, identifies at-risk individuals, allowing for timely interventions. Risk reduction strategies target modifiable factors and are essential for both preventing diabetes onset and mitigating complications. These approaches empower individuals, healthcare professionals, and policymakers to combat diabetes's increasing prevalence and its associated health and economic consequences.